Concurrent utilization of e- and h+ for water splitting to H2 and biomass components into value-added products: sustainable solar-driven photocatalysis towards meeting SDG7, 12 and 13 - Rajendran, Sivaraj; Saju, Simi; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemical Communications, 2025)
Photocatalytic water splitting is considered one of the efficient methods for producing green hydrogen. However, the sluggish oxygen evolution reaction (OER) kinetics with four electrons limits the overall efficiency of water splitting. Biomass components/biomass derivatives are renewable carbon feedstocks that are abundantly available in nature. It is prudent to make use of electrons and holes concurrently in photocatalysis for H2 production and oxidation of biomass components, respectively, due to the latter's occurrence at a lower potential (<= 1 V) than that of the OER (>1.23 V), to value-added products (VAPs); this approach makes the entire process energy-efficient and kinetically superior. This potential approach could effectively utilize the charge carriers and abundant renewable resources of water and biomass simultaneously, meeting the sustainability, energy conversion and economic goals together. Parallel utilization of the charge carriers for redox reactions also enhances the sustainability of the catalyst system employed. Interestingly, biomass component oxidation to VAPs occurs in several steps, which not only enhances hole utilization but also provides an opportunity to design better catalysts to enhance the selectivity of the target products. Carrying out such reactions under aerobic or anaerobic conditions and different pH conditions allows fine-tuning of the product selectivity. The current review provides a detailed overview of the recent developments in this emerging area with three different types of photocatalyst systems, namely, oxide-, chalcogenide-, and carbon-based materials. Among these, the oxide-based systems generally demonstrate the highest activity with sustainability, maintaining performance for several hours. While many of these systems exhibited high selectivity towards a single product, 100% selectivity to lactic acid from glycerol was observed with a BiVO4-integrated TiO2 catalyst. Finally, the challenges, opportunities and future perspectives in this thriving field are listed, and they underscore the role of a carbon-neutral economy towards achieving a potentially sustainable future.

Concurrent utilization of e− and h+ for water splitting to H2 and biomass components into value-added products: sustainable solar-driven photocatalysis towards meeting SDG7, 12 and 13 - Rajendran, Sivaraj; Saju, Simi; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemical Communications, 2025)
Photocatalytic water splitting is considered one of the efficient methods for producing green hydrogen. However, the sluggish oxygen evolution reaction (OER) kinetics with four electrons limits the overall efficiency of water splitting. Biomass components/biomass derivatives are renewable carbon feedstocks that are abundantly available in nature. It is prudent to make use of electrons and holes concurrently in photocatalysis for H2 production and oxidation of biomass components, respectively, due to the latter's occurrence at a lower potential (≤1 V) than that of the OER (>1.23 V), to value-added products (VAPs); this approach makes the entire process energy-efficient and kinetically superior. This potential approach could effectively utilize the charge carriers and abundant renewable resources of water and biomass simultaneously, meeting the sustainability, energy conversion and economic goals together. Parallel utilization of the charge carriers for redox reactions also enhances the sustainability of the catalyst system employed. Interestingly, biomass component oxidation to VAPs occurs in several steps, which not only enhances hole utilization but also provides an opportunity to design better catalysts to enhance the selectivity of the target products. Carrying out such reactions under aerobic or anaerobic conditions and different pH conditions allows fine-tuning of the product selectivity. The current review provides a detailed overview of the recent developments in this emerging area with three different types of photocatalyst systems, namely, oxide-, chalcogenide-, and carbon-based materials. Among these, the oxide-based systems generally demonstrate the highest activity with sustainability, maintaining performance for several hours. While many of these systems exhibited high selectivity towards a single product, 100% selectivity to lactic acid from glycerol was observed with a BiVO4-integrated TiO2 catalyst. Finally, the challenges, opportunities and future perspectives in this thriving field are listed, and they underscore the role of a carbon-neutral economy towards achieving a potentially sustainable future.

Mesoporous Fe2O3-TiO2 integrated with plasmonic Ag nanoparticles for enhanced solar H2 production - Mani, Sunesh S.; Rajendran, Sivaraj; Saju, Simi; Babu, Bindhya M.; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2025)
Present work describes a sol-gel assisted one-pot synthesis of mesoporous Fe2O3-TiO2 nanocomposites (TiFe) with different Ti : Fe ratios, and fabrication of Ag-integrated with TiFe nanocomposites (TiFeAg) by a chemical reduction method and demonstrated for high solar H2 generation activity in direct sunlight. Enhanced solar H2 production is attributed to the light absorption from entire UV+Visible region of solar spectrum combined with Schottky (Ag-semiconductor) and heterojunctions (TiO2-Fe2O3), as evidenced from HRTEM and various characterization studies. TiFeAg-2 thin film (1 wt % Ag-loaded TiFe-4) displayed the highest activity with a solar H2 yield of 7.64 mmol h-1g-1, which is 48 times higher than that of bare TiO2 and 5 times higher in thin film form compared to its powder counterpart. Schottky and heterojunctions formed at the interface efficiently separate the charge carriers and increase the hydrogen production activity. The highest H2 production activity of TiFeAg-2 is partly attributed to the heterogeneous distribution of Fe3+ and metallic Ag-species with relatively high Ag/Ti surface atomic ratio. A plausible photocatalytic reaction mechanism on TiFeAg nanocomposite may involve the direct electron transfer from both Fe2O3 and TiO2 to Ag nanoparticles which are subsequently utilized for the reduction of H+ to H2.
Keywords: energy conversion; green hydrogen; Photocatalysis; Solar harvesting; water splitting

Multifunctional NiO/Ti3+-TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e- and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p-n heterojunction formation between NiO and Ti3+-TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+-TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni-Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+-TiO2 nanocomposites. EXAFS studies show that the Ni-O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+-O-Ti3+/Ti4+ lattice network. Ni2+/Ti3+-TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C-C cleavage of glycerol. The NiO/Ti3+-TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+-TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h-1 g-1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+-TiO2, formation of a p-n heterojunction at the interface between NiO and Ti3+-TiO2 and effective utilization of charge carriers for redox reactions.

Multifunctional NiO/Ti3+–TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e− and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p–n heterojunction formation between NiO and Ti3+–TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+–TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni–Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+–TiO2 nanocomposites. EXAFS studies show that the Ni–O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+–O–Ti3+/Ti4+ lattice network. Ni2+/Ti3+–TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C–C cleavage of glycerol. The NiO/Ti3+–TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+–TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h−1 g−1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+–TiO2, formation of a p–n heterojunction at the interface between NiO and Ti3+–TiO2 and effective utilization of charge carriers for redox reactions.

Towards improved activity and stability in RWGS reaction: Dispersed copper in mesoporous alumina matrix as a strategy for enhanced performance - Saju, Simi; Rajendran, Sivaraj; Oztas, Ulviye; Ruiz, Sergio Carrasco; Reina, Tomas Ramirez; Ghosh, Biplab; Sree, Sreeprasanth Pulinthanathu; Meena, Raghavendra; Li, Guanna; Bobadilla, Luis F.; Vinod, Chathakudath P.; Mathew, Thomas; et al. (Chemical Engineering Journal, 2025)
The development of highly performing Cu-based catalysts with high dispersion of Cu species in nanocrystalline form on a suitable oxide support is significant in reverse water gas shift (RWGS) reaction. We report a simple and robust one-pot sol-gel synthesis of mesoporous Al10-xCuxOy (m gamma-Al10-xCux-SG) catalysts with Cu species in a highly dispersed nanocrystalline form in the gamma-Al2O3 matrix and its high catalytic performance in RWGS reaction. The lack of long range structural order of copper species in m gamma-Al10-xCux-SG catalysts evidenced from Cu-K edge extended X-ray absorption fine structure (EXAFS) studies illustrates the fine distribution of copper species in mesoporous gamma-Al2O3 lattice. Activity study revealed that m gamma-Al10-xCux-SG catalysts showed significantly high CO2 conversion to CO and excellent catalytic stability compared to gamma-Al10-xCux-I prepared by conventional impregnation method. Mesoporous Al9Cu1 (m gamma-Al9Cu1) displayed a CO2 conversion of 45 % at 500 degrees C, which is about 2.8 times higher activity than conventional gamma-Al9Cu1-I catalyst with almost same Cu loading as that of m gamma-Al9Cu1 catalyst. Stability study at 500 degrees C over a period of 50 h revealed that m gamma-Al10-xCux-SG catalysts at low Cu loading (m gamma-Al9.9Cu0.1) showed excellent catalytic stability. The strong copper-alumina interaction in m gamma-Al10-xCux-SG catalysts with enhanced number of active sites at the copper-alumina interface as evidenced from field emission scanning electron microscope (FESEM), high-resolution transmission electron microscope (HRTEM), H2-temperature programmed reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS), electrochemical characterization, and Cu-K edge EXAFS analysis enhances the activity and stability of the catalyst. Density functional theory (DFT) studies and the Operando DRIFTS-MS analysis of RWGS over m gamma-Al9Cu1 catalyst revealed that the mechanism of RWGS reaction to CO formation on m gamma-Al10-xCux-SG catalysts is preceded through the formation of a hydroxycarbonyl (OCOH) intermediate. The present synthesis strategy provides an opportunity for producing Cu-based catalysts with further enhanced activity and stability in RWGS reaction by suitable modification of the catalyst.